O Parametrach Krytycznych Względnego Ruchu Dwóch Płyt - Bogacz, R. (Engineering Transactions, 1973)
An analysis of stability of a system consisting of two plates sliding on each other at a constant velocity. The cases are considered of elastic and viscoelastic materials of the plates. The formulae determining the critical value of the relative motion of plates is given, taking into account the characteristic parameters of the system. It is shown that viscosity may substantially influence the critical velocity of motion.